2005
DOI: 10.1530/rep.1.00602
|View full text |Cite
|
Sign up to set email alerts
|

Expression and possible involvement of calpain isoforms in mammalian egg activation

Abstract: At fertilization in mammals, the spermatozoon triggers a unique signal transduction mechanism within the egg, leading to its activation. It is well accepted that the earliest event observed in all activated eggs is an abrupt rise in intracellular calcium concentrations. However, little is known regarding the downstream proteins that are activated by this rise in calcium. Calpains constitute a family of intracellular calcium-dependent cysteine proteases whose members are expressed widely in a variety of cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Protein concentrations are associated with bull fertility [101] and the mRNA is down-regulated in the endometrium of heifers which carried a pregnancy to term compared to those in which the embryo died after transfer [26]. Another gene, CAST , plays an important role in sperm capacitation and the acrosome reaction [102-104] and may play a role in oocyte calcium-mediated processes that occur during oocyte activation [105]. The same SNP in CAST found to be associated with DPR in this study was earlier associated with DPR, PL, NM and SCS [15].…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentrations are associated with bull fertility [101] and the mRNA is down-regulated in the endometrium of heifers which carried a pregnancy to term compared to those in which the embryo died after transfer [26]. Another gene, CAST , plays an important role in sperm capacitation and the acrosome reaction [102-104] and may play a role in oocyte calcium-mediated processes that occur during oocyte activation [105]. The same SNP in CAST found to be associated with DPR in this study was earlier associated with DPR, PL, NM and SCS [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that TIMP1 , OAZ1 , NUCB1 and CAPNS2 genes play important physiologic functions in follicular development (Lin et al. 2002; Ben‐Aharon et al. 2005; Mazaud et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that TIMP1, OAZ1, NUCB1 and CAPNS2 genes play important physiologic functions in follicular development (Lin et al 2002;Ben-Aharon et al 2005;Mazaud et al 2005;Clark et al 2008). The tissue inhibitors of metalloproteinase (TIM-Ps) may be regulated by the action of autocrine and ⁄ or paracrine factors synthesized in preovulatory granulosa cells in response to the LH surge (Ha¨gglund et al1999;Liu et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanistic reasons for lethality in the absence of m-calpain are still unclear. There have been several reports of m-calpain involvement in cell proliferation in certain circumstances, including reports of its involvement in chromosome segregation during mitosis [ 44 ] as well as during meiosis [ 45 ]. Defects in migration, reported in Capn4 -/- cells [ 9 ], could contribute to failed embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm binding to the oocyte leads to increased cytoplasmic calcium which triggers the acrosome reaction [ 46 ]. Both μ- and m-calpain have recently been detected in rodent sperm [ 47 ] and oocytes [ 45 ]. m-calpain was implicated in the acrosome reaction [ 47 ] which correlated with a translocation of m-calpain to the cortical membrane in oocytes where it might participate in the release of cortical granule contents required to prevent polyspermy [ 45 ].…”
Section: Discussionmentioning
confidence: 99%